Perempuan dan Kepemimpinan di Ranah Politik: Tinjauan Tafsir Al-Quran di Indonesia Abad 21: Women and Leadership in the Political Sphere: A Review of Quranic Interpretation in 21st Century Indonesia - Fauzan Ashar Nur Huda (DIRASAH: Jurnal Kajian Islam, 2024)
This study examines the views of Indonesian Qur'anic interpretations regarding female leadership in politics, focusing on the interpretation of Surah At-Taubah verse 71. The study primarily highlights the Kemenag (Ministry of Religious Affairs) interpretation, which is perceived as limiting women's roles in political leadership. This interpretation is compared with more inclusive contemporary interpretations that offer greater opportunities for women in public and political spaces. The research employs a qualitative method with a content analysis approach to examine 21st-century Qur'anic interpretations, which align with the growing awareness of gender issues in Indonesia. The findings show that 21st-century interpretations tend to be more inclusive and provide legitimacy for women's participation in politics, although some interpretations maintain traditional views that restrict women's roles. These findings have significant implications for the development of gender equality discourse in Indonesia, particularly in the context of female leadership in politics.